Determinants and Clinical Significance of Musculoskeletal Symptoms in Patients With Chronic Graft-Versus-Host Disease. Issue 6 (31st May 2022) - Zelic Kerep, Ana; Pirsl, Filip; Steinberg, Seth; Mitchell, Sandra; Curtis, Lauren; Holtzman, Noa; Goklemez, Sencer; Bilic, Ervina; Cowen, Edward; Pichard, Dominique; Joe, Galen; Comis, Leora; et al.
Abstract : Musculoskeletal symptoms in chronic graft-versus-host disease (cGVHD) are rare manifestations contributing to disease burden. This study assesses the frequency of muscle cramps, joint and muscle aches, and muscle weakness in a cohort of patients severely affected by cGVHD. Three hundred thirty-four patients participated in the NCI natural history study of cGVHD (NCT00092235) from October 2004 to March 2017. Five-point Lee cGVHD Symptom Scale was dichotomized (less symptom bother—0, 1, 2; severe symptom bother—3, 4) and tested for associations with: Short Form 36 (SF36), 2-minute walk test, grip strength, joint range of motion, and human activity profile, clinical and laboratory data. Seventy-five point four percent of patients reported joint and muscle aches (36.8% severe, Lee Symptom Scale score 3–4), 74.3% muscle cramps (33.5% severe), and 82.34% muscle weakness (45.51% severe), which were associated with reduced functional capacity (SF36 Physical Component Scale, P < 0.0001). Muscle cramps were associated with limited joint movement ( P < 0.0001) and skin manifestations (skin thickening, P = 0.0008; itchy skin, P = 0.0003). Muscle cramps did not show association with potential causative agents, such as concomitant calcineurin inhibitors therapy, statins, or use of antidiabetic drugs. Joint and muscle aches showed associations with multiple variables (including strong associations with mood symptoms and fatigue, P < 0.0001). Muscle weakness was not associated with steroid dose, but was significantly associated with depression ( P < 0.0001) and anxiety ( P = 0.0009). This study documents a high frequency of musculoskeletal symptoms in a cohort of adult patients with cGVHD. The multivariable logistic regression models showed that a joint set of factors were moderately well associated with musculoskeletal symptoms in this study.